2nd Mexican Consensus of Endovenous Chemical Ablation (Scleorotherapy) 2018 - Vega Rasgado, F.; Ángel López Paredes, J.; Serralde Gallegos, J. A.; Bolaños Celaya, D.; Ramírez Cadena, C.; Alberto Cavazos Ortega, M.; Lira Rodríguez, O.; Rendón Elías, F.; Contreras Cisneros, F.; Lugo Ramírez, A.; Jiménez Gorena, E. (Phlebologie, 2019)
Background Sclerotherapy has been carried out since 1516 and is accepted and performed worldwide according to many references from books and journals. Mexican doctors participated in other consensuses in order to obtain various agreements, references, methods and procedures that are universally accepted to establish this document, including the European consensus of sclerotherapy 2003 and its last revision in 2006, the Clinical practice guidelines for prevention, diagnosis and treatment of chronic venous insufficiency in 2009 in México, the Argentine and Latin American consensus for sclerotherapy in 2012, European sclerotherapy guidelines in chronic venous diseases of 2013,and various literature sources as well. The first Mexican consensus on sclerotherapy published in January 2014 which was reviewed and updated in this document.Objective Review and update the general bases of Endovenous Chemical Ablation (ECA) also known as Sclerotherapy, according to evidence-based medicine updating the previously published consensus.Method General questions about Endovenous Chemical Ablation (ECA) were established concerning: indications, contraindications, types of sclerosing agents and the concentrations used, patient position, methods of application, way to prepare and preserve the sclerosants, necessary equipment, injection volumes, differents administration ways, compressive therapy and special comments. To answer these questions the existing literature and the topics in which the reports showed uniformity were consulted. A panel of experts was constituted who provided their personal experience, the answers were formulated in the form of clinical guidelines or general recommendations to provide concrete answers to the specific questions, in some issues we include possible accepted variations.
Keywords: Sclerotherapy; consensus; endovenous chemical ablation (ECA)